Internal rotations in stannabutadienes : a DFT study - Liu, Qing. (2009)
In this project, two different parts of theoretical calculation are involved. The first part focuses on the computational study of the internal rotation potential energy surfaces (PESs) of nine stannum substituted butadienes, at the level of B3LYP/LanL2DZ. For molecules including the Sn=Sn double bond, the most stable molecular structure adopts a gauche conformation. The internal rotation barriers follow the trend: 1,4-distannabutadiene > 1-stannabutadiene > 1,2.4-tristannabutadiene > tetrastannabutadiene > 1,3-distannabutadiene = 1,2-distannabutadiene > 1,2,3-tristannabutadiene > 2,3-distannabutadiene > 2-stannabutadiene. The second part systemically studies the ring strain, π-σ hyperconjugation and ring-opening reaction of the silicon-substituted cyclobutenes at the level of B3LYP/6-311+G(d,p). The strengths of ring strains are characterized by the bond angle deviation from the normal angle of hybrid orbitals. The positions of strong bent σ bonds are regarded as an important factor that causes different strains of silacyclobutenes. The thermal ring opening reactions of monosilacyclobutenes and disilacyclobutenes are predicted to possess a symmetry-allowed conrotatory mechanism. The reactive heats show that 1,2-disilacyclobut-3-ene is significantly more stable than 1,4-silabutadiene, while silacyclobut-1-ene is less stable than 2-silabutadiene.